STRATEGI KOMUNIKASI MAHASISWA ASING DALAM INTERAKSI DAN PEMBELAJARAN BAHASA INDONESIA (Studi Kasus Mahasiswa Program Darmasiswa Undip Tahun 2010/2011) - Eva Ardiana Indrariani (Master Program in Linguistics, Diponegoro University, 2011)
Ethnography of communication is a very important method of doing a research project on learning Indonesian as a foreign language. This study will describe what learners have to take into account when communicating appropriately and effectively in a discourse community. It tries to describe communication strategies of twelve foreign students, who participate in the program of Darmasiswa Undip 2010/2011, when interacting with Indonesian native speakers. They perform a variety of communication strategies in order to make their interactions more communicative. Keywords : ethnography of communication, communication strategies, foreign speakers, learning, Indonesian language